Oxidation of commercial petronas diesel with tert-butyl hydroperoxide over polymolybdate alumina supported catalyst modified with alkaline earth metals - Wan Abdullah, Wan Nazwanie (Malaysian Society of Analytical Sciences, 2016)
Due to strict environmental legislation for ultra-low sulfur diesel fuels, increasing technical and operational challenges are imposed to conventional hydrodesulfurization (HDS) technology. Therefore, catalytic oxidative desulfurization (Cat-ODS) has been suggested to be an alternative method to replace a conventional method which is hydrodesulfurization. In this study, catalytic oxidation of commercial diesel was performed using an oil-soluble oxidant, tert-butyl hydroperoxide (TBHP), over polymolybdate supported on alumina MoO3-PO4/Al2O3 catalyst. A commercial Petronas diesel with 440 ppmw of total sulfur was employed to evaluate the elimination of sulfur compounds. Besides, the percentage of sulfur removal was measured by (GC-FPD). Alkaline earth metals, such as Calcium (Ca), Barium (Ba) and Strontium (Sr) were introduced on the surface of MoO3-PO4/Al2O3. The results showed that the catalytic activity decreased in the order, Ca/MoO3-PO4/Al2O3>Sr/MoO3-PO4/Al2O3> Ba/MoO3-PO4/Al2O3. The Ca/MoO3-PO4/Al2O3 catalyst was characterized by XRD and FESEM. XRD results showed that the best catalyst was highly amorphous while FESEM micrograph illustrated an aggregation and agglomeration of various particle sizes. The catalytic activity of Ca/MoO3-PO4/Al2O3 catalyst with various Ca/Mo ratios were also studied. When the Ca/Mo ratio was 15:85, the sulfur removal was the highest (79%) at 45°C, 30 min and O/S molar ratio 3.0 with solvent = dimetylformamide (DMF), diesel/solvent ratio = 1.0.